Optomechanics with a hybrid carbon nanotube resonator - A. Tavernarakis (Nature Portfolio, 2018)
Optomechanics has recently moved into the quantum regime. Here, Tavernarakis et al. demonstrate that a hybrid optomechanical device made up of a carbon nanotube with a metal nanoparticle at its tip can push force measurements towards the quantum regime at room temperature.